2021
DOI: 10.1371/journal.pone.0261417
|View full text |Cite
|
Sign up to set email alerts
|

Clearing-induced tisssue shrinkage: A novel observation of a thickness size effect

Abstract: The use of clearing agents has provided new insights in various fields of medical research (developmental biology, neurology) by enabling examination of tissue architecture in 3D. One of the challenges is that clearing agents induce tissue shrinkage and the shrinkage rates reported in the literature are incoherent. Here, we report that for a classical clearing agent, benzyl-alcohol benzyl-benzoate (BABB), the shrinkage decreases significantly with increasing sample size, and present an analytical formula descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In many clearing protocols, such as iDISCO+, the solvents result in the expansion or shrinkage of the tissue samples ( 1 ). While some studies report shrinkage in all dimensions hereby maintaining similar spatial distribution, others suggest different amounts of shrinkage for different tissues, which could warp the original tissue and organ structure ( 19 , 25 , 26 ). On the other hand, tissue shrinkage can also benefit imaging depth as it renders larger samples smaller.…”
Section: Discussionmentioning
confidence: 94%
“…In many clearing protocols, such as iDISCO+, the solvents result in the expansion or shrinkage of the tissue samples ( 1 ). While some studies report shrinkage in all dimensions hereby maintaining similar spatial distribution, others suggest different amounts of shrinkage for different tissues, which could warp the original tissue and organ structure ( 19 , 25 , 26 ). On the other hand, tissue shrinkage can also benefit imaging depth as it renders larger samples smaller.…”
Section: Discussionmentioning
confidence: 94%
“…In the present cases, although minor morphological changes due to shrinkage were confirmed, we observed no significant effects in terms of histopathological evaluation and diagnosis. This may have been because our sample sizes were relatively large, as Vulders et al have recently suggested that large samples tend to shrink less after solvent‐based tissue clearing [24]. Regarding immunohistochemical staining, although we did not perform such examinations on cleared tissues, it has been shown that ethyl cinnamate‐based TOC is compatible with immunohistochemical labeling [15].…”
Section: Discussionmentioning
confidence: 99%
“…Large microglial image datasets can also be obtained via light-sheet microscopy used in conjunction with methods to clear brains containing fluorescently labeled microglia. This approach ensures intact microglial architecture and enables global analysis of microglial morphotypes without sectioning artifacts; however, with the caveat that the shrinkage which occurs during sample preparation will alter microglial profiles ( Bekkouche et al, 2020 ; Vulders et al, 2021 ). Furthermore, light-sheet technology has modest spatial resolution which does pose an issue for researchers wanting to capture finer microglial processes in their morphometric analysis ( Watkins and St. Croix, 2018 ; Chen et al, 2022 ).…”
Section: Tools For Imaging Stained/labeled Microglia In Situmentioning
confidence: 99%